SOSIALISASI POLA ASUH ANAK DAN REMAJA OLEH MAHASISWA KELOMPOK 3 KKN NUSANTARA 2025: UPAYA PEMBERDAYAAN IBU-IBU DASAWISMA PADUKUHAN SAYANGAN, KULON PROGO, D.I.YOGYAKARTA - Sizil Azzahra Sa'dillah; Wanda Iqwatul Qofifah; Rahmadhini Zaizafun; Erica Layla Usman; Muhammad Roihan Qowima; Achmad Faiq Ramadhan; Dhimas Risky Nur Firmansyach (CV. Denasya Smart Publisher, 2025)
This community service article aims to improve the understanding and skills of mothers in Dasawisma in Dukuh Sayangan, Kulon Progo Regency, in applying positive and effective parenting patterns for children and adolescents through an interactive socialization approach. The method used is a qualitative, descriptive, participatory approach, involving participatory observation, focused group discussions (FGD) with 30 participants, and a systematic literature review to support the theoretical foundation of authoritative, permissive, and authoritarian parenting styles. The socialization results showed full participation with high enthusiasm, where the mothers were able to summarize the characteristics of authoritative, permissive, and authoritarian parenting styles after the thematic lecture, and understood the impact of communication and firmness in building family cohesion and the role of parenting in feeding interventions to prevent stunting. Group discussions identified the main barriers, limited time, access to information, cultural norms, and low understanding of child protection laws, and developed local adaptation strategies in the form of peer support forums, traditional media containing summaries of child protection laws, and visual aids for safe zones for children. The implications of the socialization were reflected in increased self-confidence and the formation of informal support networks. This parenting socialization effectively equipped Dasawisma mothers with knowledge and social networks for practice change, so it is recommended to continue through regular forums, local language guide modules, village facilitator training, and program integration at posyandu and social and cultural activities.